2020
DOI: 10.1108/md-06-2019-0701
|View full text |Cite
|
Sign up to set email alerts
|

How user-driven innovation and employee intrapreneurship promote platform enterprise performance

Abstract: PurposeThe purpose of this study is to investigate the impact of user-driven innovation (UDI) and employee intrapreneurship (EI) on the innovation performance of platform enterprises through the mediating role of market intelligence responsiveness (MIR) and the moderating role of knowledge and information resource acquisition (KRA and IRA, respectively) between MIR and innovation performance. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 85 publications
3
27
0
Order By: Relevance
“…For example, Marvel et al ( 2007 ) showed that intrapreneurial employees (i.e., employees who actively engage in venture and strategic renewal behaviors) in the technical sector were responsible for the creation, promotion, and implementation of several breakthrough innovations for their organization. Moreover, Camelo-Ordaz et al ( 2012 ) reported similar results in their study among intrapreneurial employees in the creative industry, as well Wan et al, ( 2020a , 2020b ) in platform enterprises.…”
Section: Theoretical Background and Hypothesessupporting
confidence: 65%
See 1 more Smart Citation
“…For example, Marvel et al ( 2007 ) showed that intrapreneurial employees (i.e., employees who actively engage in venture and strategic renewal behaviors) in the technical sector were responsible for the creation, promotion, and implementation of several breakthrough innovations for their organization. Moreover, Camelo-Ordaz et al ( 2012 ) reported similar results in their study among intrapreneurial employees in the creative industry, as well Wan et al, ( 2020a , 2020b ) in platform enterprises.…”
Section: Theoretical Background and Hypothesessupporting
confidence: 65%
“…The intrapreneurship of primary health care professionals promotes the innovation outputs (β Innov.Int = 0.523; p < 0.001). Other empirical studies have identified this positive relationship between intrapreneurship and innovation (e.g., Wan et al, 2020a , 2020b ).…”
Section: Discussion Of Results: Intuition and Rationality In Intrapreneurship And Innovation Outputs Of Health Professionals In Primary Hmentioning
confidence: 75%
“…Relevant research has focused mainly on trading platforms that connect bilateral and multilateral markets (Dimakopoulos and Sudaric, 2018). Research on internal platform enterprises (Intrapreneurship mechanism) that have transformed from traditional manufacturing and service-oriented enterprise groups is inadequate (Chen et al, 2020;Wan et al, 2020). Employee intrapreneurship forms an essential mode of operation for platform enterprises and is the primary element in driving enterprise innovation (Wan et al, 2020;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Uppsala model emphasizes the active role of entrepreneurs in assuming that firms are not averse to risk to internationalize and the necessary knowledge to enter new markets progress is possibly offered by a firm experience concerning overseas activities (Johanson and Vahlne, 1990). Firm competitiveness, especially the knowledge-intensive business, is linked to its talent base and embeddedness in international networks providing business opportunities (Wan et al , 2020). Based on the resource-based view perspective, firm internationalization is dependent on valuable, hard-to-imitate and irreplaceable resources that contribute to a company’s core or unique competencies and lead to long-term competitive advantage (Hart, 1995).…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%